Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights - Thorsten Blecker; Wolfgang Kersten; Christian M. Ringle (epubli GmbH, 2015)
This volume contains research contributions by an international group of authors focusing on innovative models to optimize logistics and supply chains at an operational level. They address process efficiency and data-related aspects. Supply chain security insights are also given.
urn:nbn:de:gbv:830-88213459; https://econpapers.repec.org/RePEc:zbw:hiclch:209279; https://econpapers.repec.org/RePEc:zbw:hiclch:209280; https://econpapers.repec.org/RePEc:zbw:hiclch:209281; https://econpapers.repec.org/RePEc:zbw:hiclch:209282; https://econpapers.repec.org/RePEc:zbw:hiclch:209283; https://econpapers.repec.org/RePEc:zbw:hiclch:209284; https://econpapers.repec.org/RePEc:zbw:hiclch:209285; https://econpapers.repec.org/RePEc:zbw:hiclch:209286; https://econpapers.repec.org/RePEc:zbw:hiclch:209287; https://econpapers.repec.org/RePEc:zbw:hiclch:209288; https://econpapers.repec.org/RePEc:zbw:hiclch:209289; https://econpapers.repec.org/RePEc:zbw:hiclch:209290; https://econpapers.repec.org/RePEc:zbw:hiclch:209291; https://econpapers.repec.org/RePEc:zbw:hiclch:209292; https://econpapers.repec.org/RePEc:zbw:hiclch:209293; https://econpapers.repec.org/RePEc:zbw:hiclch:209294; https://econpapers.repec.org/RePEc:zbw:hiclch:209295; https://econpapers.repec.org/RePEc:zbw:hiclch:209296; https://econpapers.repec.org/RePEc:zbw:hiclch:209297; https://econpapers.repec.org/RePEc:zbw:hiclch:209298
Keywords: 650; Logistics; Supply Chain Management; Supply Chain; Supply Chain Security; Data-driven Process Management; Supply Chain Operations